Factores Psicosociales que Influyen en la Calidad de Vida de los Docentes de la Facultad de Psicología de la Universidad Antonio Nariño (2021)
This research describes the correlation between quality of life, lifestyles, sociodemographic variables, burnout and workload, through the implementation of the instruments "Perception of the quality of life of teachers of the Faculty of Psychology of the Antonio Nariño University ”and the Fantastic questionnaire